Improving Speaking Ability Through Picture Card Assisted Storytelling Method For Children 5-6 Years Old In Kindergarten: Peningkatan Kemampuan Berbicara Melalui Metode Bercerita Berbantuan Media Kartu Gambar Pada Anak Usia 5-6 Tahun Di Taman Kanak - Fitri Nailul Izzah; Luluk Iffatur Rocmah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to improve the speaking ability of children aged 5-6 years in Mutiara Hati Krian Sidoarjo Kindergarten through storytelling method assisted by picture card media. This type of research is Classroom Action Research (CAR) which is carried out in two cycles with three meetings in each cycle. The data collection technique used is descriptive quantitative and descriptive qualitative. The indicator of success in this study is if the average value of children's speaking ability through storytelling method assisted by picture card media has reached the very well developed criteria (BSB) with a percentage of 75%-100%. The results of this study indicate an increase in children's speaking skills through storytelling methods assisted by picture card media at Mutiara Hati Krian Sidoarjo Kindergarten gradually from pre-cycle, first cycle and second cycle. This is evidenced by the increase in the average speaking ability of children in the pre-cycle by 33%, increasing to 58% in the first cycle of action and reaching 92% in the second cycle of action. The results of this study are expected to provide information to institutions that handle early childhood or the general public who need information about the application of picture card-assisted storytelling methods to improve speaking skills in children aged 5-6 years. Keywords - Speaking Ability, Storytelling Method, Cards Picture